The Urgency of Pre-Marital Education for the Community in the Context of Suppressing Household Divorce Rates in West Java, DKI Jakarta and Banten - Dewi Sulastri; Neni Nuraeni; Zulbaidah Zulbaidah; Neng Yani Nurhayani; Enceng Arif Faizal (Westscience Press, 2023)
This study aims to examine the urgency of premarital education as a preventive effort in reducing divorce rates in West Java, DKI Jakarta, and Banten. The research method used is the literature review method, which involves an in-depth analysis of various relevant literature sources. The results showed that premarital education has a crucial role in preparing prospective couples to face the challenges of married life. Through a deep understanding of values, effective communication, and conflict resolution skills, couples can build a solid foundation for a sustainable marriage relationship. This study also identified various supporting and inhibiting factors for the implementation of premarital education in the region. These findings provide valuable insights for the development of premarital education programs that are more effective and can be widely adopted in the community. The implications of this research can help the government, educational institutions, and related parties to design policies that support improving the quality of marriage relationships and reducing divorce rates in society.